Biophysical interplay between extracellular matrix remodeling and hypoxia signaling in regulating cancer metastasis - Lee, Sun-Ah; Cho, Gi-Ju; Kim, Doyoung; Kim, Dong-Hwee (Frontiers in Cell and Developmental Biology, 2024)
Mechanical properties of the tumor microenvironment play a critical role in cancer progression by activation of cancer mechano-responses. The biophysical interactions between cancer cells and their dynamic microenvironment are attributed to force-dependent alterations in molecular pathways that trigger the structural reorganization of intracellular organelles and their associated genetic modifications. Recent studies underscore the role of oxygen concentration in cancer metastasis. Suppressed oxygen levels promote the development of invasive phenotypes and aggressive proliferation of cancer cells, accompanied by remodeling of tumor microenvironment encompassing the modulation of physical settings of extracellular matrix. This review summarizes the role of biophysical interactions between cancer cells and their surroundings in determining cancer progression. Biophysical interpretation of the tumor microenvironment and cancer progression could provide further insights into the development of novel biomedical technologies for therapeutic cancer treatment.